KARAKTERIKSTIK ASPAL YANG DIPERLUKAN SEBAGAI BAHAN JALAN - M. Sjahdanulirwan (Direktorat Bina Teknik Jalan dan Jembatan, 2003)
Nowadays, many types of asphalt have been used on road construction, either from domestic production or imported. Understanding of asphalt characteristics is required to determined the types of asphalt needed in accordance with its requirement. Beside penetration index, the adhesion, softening point, and maltene parameter will strongly influenced the asphalt performance on pavement mix. To fulfil the demanding quality of asphalt on road construction, the asphalt producers should have cooperation with many parties, such as additive suppliers, research and development institutions, or universities, and maintaining the ashalt quality up to project location. This paper describe more detail about asphalt characteristics, especially for penetration grade asphalt.